Observational Study of Dynamic Splints on Daily Activity Task Achievement for Children with Spastic Cerebral Palsy - Triyani, Triyani; Anatasia, Suci; Rizqi Pranoto, Luthfi; Rizal, Ahmad Syamsul (Poltekkes Kemenkes Jakarta I, 2024)
Background: Cerebral palsy is a developmental brain disorder that leads to decreased motor function of the extremities, especially on the hands. The provision of dynamic splints would be expected over time to contribute to functional hand improvement, such as gross motor function. Aims: To observe the time in daily activity achievement for patients with spastic cerebral palsy while wearing dynamic hand orthosis. Methods: Quantitative with pre-test post-test design. Ten CP children with an age range of 8 - 17 years with mild to moderate spasticity were observed before wearing and after wearing dynamic hand orthosis to do 7 tasks (Jebsen-Taylor Hand Function Test). Results: After 2 weeks wearing the device, all participants showed different results indicating an improvement of 5.5 seconds to all tasks on the Jebsen Taylor Hand Function Test. Conclusion: Dynamic splints have an influence on increasing the time to complete the tasks, thus can be considered along with regular exercise.